Personality Traits, Technology Adoption, and Technical Efficiency : Evidence from Smallholder Rice Farms in Ghana - Ali, Daniel Ayalew; Bowen, Derick; Deininger, Klaus (World Bank, Washington, DC, 2017)
Although a large literature highlights the impact of personality traits on key labor market outcomes, evidence of their impact on agricultural production decisions remains limited. Data from 1,200 Ghanaian rice farmers suggest that noncognitive skills (polychronicity, work centrality, and optimism) significantly affect simple adoption decisions, returns from adoption, and technical efficiency in rice production, and that the size of the estimated impacts exceeds that of traditional human capital measures. Greater focus on personality traits relative to cognitive skills may help accelerate innovation diffusion in the short term, and help farmers to respond flexibly to new opportunities and risks in the longer term.